KEPASTIAN HUKUM SISTEM PUBLIKASI DALAM PENDAFTARAN TANAH DI INDONESIA MENURUT UU RI NOMOR 5 TAHUN 1960 TENTANG POKOK-POKOK AGRARIA - I Dewa Ayu Widyani (to-ra, 2015)
The purposes of this paper is in order to know about the publication system in enrolling the land that be followed by Indonesia and the form of law protection that can be given to the holder of right. From the description of the writing can be concluded whereas the publication system in enrolling the land is the negative system that contain of positive element. In solving about the weakness of this publication system, so be decided in PP24/1997 Article 32 point (2) namely in the matter about the land that have been issued its certificate on behalf of someone or the law institution that getting it by the good willingness and factually master it, so that the other party who feel have an authority of such land, cannot claim again about the implementation of it right. If in term of time about five (5) years during be issued the certificate do not applied the objection.